The effect of company growth, asset structure, and profitability on debt policy - Wahyu Setianingsih Nurohmah; Triyono (Proceeding International Conference on Accounting and Finance, 2023)
The goal of this study is to examine how firm growth, asset structure, and profitability affect debt policy. The population of this study consists of the 26 manufacturing enterprises in the subsector of the food and beverage industry that were listed on the Indonesia Stock Exchange (IDX) between 2018 and 2021. A total of 23 companies were selected for sampling using the purposive sampling approach, and quantitative methods were used to collect the data. The method of analysis used multiple linear regression analysis. The findings revealed that profitability had a substantial negative impact on debt policy, whereas firm expansion and asset structure had a considerable favorable impact. The findings of this study can be taken into account by businesses when deciding whether to use internal or external finances for their debt strategies.